STUDI PERBANDINGAN SISTEM PENDIDIKAN DI INDONESIA DENGAN SINGAPURA - Dessy Mega Harumawati; Istiq'faroh, Nurul; Alfi Muhimmah, Hitta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to compare the education systems in Indonesia and Singapore in order to identify the fundamental differences, strengths and weaknesses of each system. The research method used in this paper is a literature review which emphasizes the study of appropriate literature as an analytical tool for the issues raised in this research. Data sources include books, journals, papers, articles and other scientific works that are relevant to the object of this research. The results of this research show that Singapore has a more structured and standardized education system with a focus on the quality of the learning process, as well as the development of 21st century skills. In addition, a strict teacher selection and training system as well as adequate facilities and infrastructure also support the effectiveness of learning in Singapore. On the other hand, the education system in Indonesia has made various improvements, including curriculum reform and increasing teacher competency. This comparison reveals that although both countries have the same goal of improving the quality of education, the approaches used differ significantly. This research is expected to provide insight for policy makers and education practitioners in developing more effective strategies to improve the quality of education in Indonesia, by learning from the best practices implemented in Singapore.